Application of Cycle Learning Learning Strategies with Metamorphosis Material to Improve Learning Ability of Elementary Students - Hasny Delaila Siregar (Yayasan Zia Salsabila, 2022)
This study aims to describe the results of applying Cycle Learning learning strategies to elementary age children in improving students' learning abilities. In this study the learning model used is one that can stimulate student participation and the teacher acts as a facilitator. The Cycle Learning learning model is a constructivist learning model, in which learning activities are directed at student activities. This research uses a type of qualitative research with descriptive methods. The supporting factors for implementing the Cycle Learning learning strategy are: (1) Stimulating students to remember what has been taught before, (2) Motivating students to learn more and be more curious, (3) Train students to learn to find concepts through experimental activities and communicate verbally the concepts they learn and students are able to convey these concepts orally. In addition to the supporting factors, there are also inhibiting factors from the application of Cycle Learning, namely: (1) The effectiveness of learning is low if the teacher does not master the material and learning steps, (2) Demands the seriousness and creativity of teachers in designing and implementing the learning process, (3) ) Requires more time and energy as well as more planned and organized class management. The results of this study regarding the application of the learning cycle model in elementary schools can improve student learning outcomes with the aim of giving students time to think, search, find and explain examples of the application they are learning.